Vlijanie programmy social'noj podgotovki na social'nye navyki junych basketbolistov - Sniras, S. A.; Malinauskas, R. K.; Jatjavicus, D. M. (Fiziceskaja Kultura: vospitanie, obrazovanie, trenirovka, 2005)
The purpose of the research was to define the level of social skills of basketball-playing schoolchildren before the social training program and after it. The following research methods were applied: social skills inventory, mathematical statistics. Schoolchildren were asked to evaluate the following social skills: to console, to help, not to pretend, not to cheat, not to humiliate, not to revenge, to keep given word, to bear responsibility for own actions. All the procedures were carried out at the serial selection. V. Chomicius basketball school in Kaunas. The experiment was performed with 54 basketball-playing schoolchildren (with ages ranging from 13 to 15), whom we divided in an experimental group (26 schoolchildren) and a control group (28 schoolchildren). Statistically significant differences were established in the experimental group after the social training program. The level of social skills (to console, to help, not to pretend, not to cheat, not to humiliate, not to revenge, to bear responsibility for own actions) of the experimental group were improved.